2011
DOI: 10.1037/a0023488
|View full text |Cite
|
Sign up to set email alerts
|

People–things and data–ideas: Bipolar dimensions?

Abstract: We examined a longstanding assumption in vocational psychology that people-things and data-ideas are bipolar dimensions. Two minimal criteria for bipolarity were proposed and examined across 3 studies: (a) The correlation between opposite interest types should be negative; (b) after correcting for systematic responding, the correlation should be greater than -.40. In Study 1, a meta-analysis using 26 interest inventories with a sample size of 1,008,253 participants showed that meta-analytic correlations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 69 publications
(144 reference statements)
3
51
0
Order By: Relevance
“…The negative relationship between neuroticism and conscientiousness also matches the size and direction of relationships in existing literature (e.g., Beckmann, Wood, & Minbashian, 2010;Lee, Kelly, & Edwards, 2006). The intercorrelations between interests in this study were around .10 lower than found in other past research (Tay, Su, & Rounds, 2011.) The lower intercorrelations may be due to the ipsative nature of the interest measures.…”
Section: Resultssupporting
confidence: 88%
“…The negative relationship between neuroticism and conscientiousness also matches the size and direction of relationships in existing literature (e.g., Beckmann, Wood, & Minbashian, 2010;Lee, Kelly, & Edwards, 2006). The intercorrelations between interests in this study were around .10 lower than found in other past research (Tay, Su, & Rounds, 2011.) The lower intercorrelations may be due to the ipsative nature of the interest measures.…”
Section: Resultssupporting
confidence: 88%
“…We hypothesized that personality or individual difference variables may be partially responsible and interact with these sex differences. We focused on the individual's level of orientation toward both persons and things in their environments (Person-Thing Orientation: Graziano, Habashi, & Woodcock., 2011;Lippa, 1998;Little, 1968;Tay et al, 2011). We found that women engineering majors were on average lower in Thing Orientation than men, and that Thing Orientation was a significant predictor of intention to pursue a research-oriented engineering career for women.…”
Section: Journal Of Engineering Education 101 (July 2012)mentioning
confidence: 70%
“…The bivariate correlation of Person and Thing Orientations in our sample indicated that they are independent constructs (r ϭ Ϫ.06, residual r ϭ .19). Once the common variance is removed, a negative residual correlation of the magnitude of r > .40 would be expected for constructs that are ends of a bipolar continuum (Tay et al, 2011). Preliminary analyses of undergraduate involvement in research and intention to pursue a research career across the three STEM disciplines in our study revealed that students in Life Sciences (M ϭ 3.82 on a 1-5 scale) and Psychological Sciences (M ϭ 3.52) were significantly more likely than those in engineering (M ϭ 2.95) to participate in research as undergraduates.…”
Section: Preliminary Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that interest in STEM is highly responsive to environmental influences (Cheryan et al 2009, 2011; Murphy et al 2007; Stout et al 2011). Questions have also been raised concerning the validity and reliability of measures commonly used in this line of research, such as the person-thing construct and similar bipolar interest scales (e.g., data-ideas) (Tay et al 2011; Valian 2014). Further, although gender differences in work-life preferences are pervasive, they do not explain gender gaps in STEM interest or participation (Xie & Shauman 2003; Frome et al 2006, 2008; Cech et al 2011; Riegle-Crumb et al 2012; Perez-Felkner et al 2012; Morgan et al 2013; Mann & DiPrete 2013).…”
Section: Gender and Stem Educationmentioning
confidence: 99%